Which elite? Whose university? Britain’s civic university tradition and the importance of place - Whyte, W (Kongelige Danske Videnskabernes Selskab, 2017)
By any accepted measure, Britain’s universities have been the universities of an elite. But Britain did not have one elite; nor a single university system. In this essay, I attempt to go beyond a narrow focus on Oxford and Cambridge and to examine how the civic – or ‘redbrick’ – universities operated. They were, I argue, the product of a particular sort of social elite: the urban middle class of mid- to late-nineteenth century Britain. They thus reflect the fact of a divided social elite in Britain. Whilst Oxford and Cambridge were for the aristocracy, the Anglican, and the landed; the universities of the great industrial cities were intended to cater to a very different constituency. But – and this is worth stressing – it was an elite constituency nonetheless. For our purposes, this draws attention to the need for historians to recognize the existence of multiple, competing elites; and to explore what impact this has on their universities. Secondly, and still more importantly, these civic foundations foreground a theme all too often ignored in the history of universities: the importance of place. The story I set out is about geography just as much as it is history: about elites concentrated in and controlling different parts of the country and different cities, and producing different sorts of institution as a result.